Utilization of Automatic Speech Recognition Technology in English Language Teaching: A Systematic Review (2020-2023) - Alazwari, Dina Mohammed (Journal of Curriculum and Teaching Methodology, 2024)
This study aimed to conduct a systematic review to identify recent trends in utilizing Automatic Speech Recognition (ASR) technology in English language education. The current review targeted studies published between 2020 and 2023, retrieved from the ERIC database. Out of 35 studies, the review included 11 studies, following the PRISMA model for methodological analysis. The results demonstrated the effectiveness of employing ASR technology in English language education, particularly in enhancing pronunciation and speaking skills. However, the findings also indicated a scarcity of research focusing on reading and writing skills. The study revealed variations in sample selection between elementary and university students, with a noticeable absence of research directed towards middle and high school age groups. The educational significance of utilizing ASR technology to enhance the learning experience was highlighted, emphasizing the provision of enjoyable and user-friendly experiences, along with immediate feedback and students’ autonomy in the learning process. The study recommended expanding the scope of research to encompass various educational stages to better understand the impact of ASR technology on different age groups within the language learning context. Additionally, the research advocated for promoting the use of ASR technology to improve other language skills such as reading and writing. Encouraging the use of applications to stimulate self-directed learning, thus fostering students’ autonomy, was also recommended to enhance the overall learning experience.